Pendampingan Penguatan Literasi Santri dan Alumni Pesantren Tebuireng - Munawara Munawara; Ainun Fitri Mughiroh (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Recently, technological developments have become increasingly complex, strengthening literacy has become a very important aspect to ensure that Islamic boarding schools remain relevant and able to adapt to global challenges. Strengthening literacy in this case is not only for students, but also alumni to continue to develop it outside the Islamic boarding school, either through written work, design, audio visuals or other works that can advance Islamic culture and knowledge in Islamic boarding schools. This day-long literacy training or sharing program invited students representing all Tebuireng Islamic Boarding School units to actively contribute to the field of literacy, by presenting alumni who are active in the media who now have extraordinary experience in the field of literacy. This assistance and training to strengthen literacy is to support the Islamic boarding school's literacy culture to remain alive and develop in line with technological developments. This mentoring method brings students and alumni together to share and exchange experiences and work in the field of literacy. The results of this coaching and training show that: 1) Tebuireng Islamic Boarding School has succeeded in integrating literacy culture into daily activities through the formation of an active literacy community. 2) Tebuireng Islamic Boarding School proactively involves students and alumni in various literacy programs. 3) Tebuireng Islamic Boarding School organizes various literacy support programs through digital media such as websites, social media platforms, magazines and book publishing.